Comparison of Tzanakis and Alvarado scoring system in diagnosis of acute appendicitis, with Histopathology as gold standard - Muhammad Zafar Iqbal, Malik Irfan Ahmed, Naveed Akhtar Malik, Ali Kamran, Muhammad Umar Qaiser, Samra Riaz, Muhammad Zafar Iqbal, Malik Irfan Ahmed, Naveed Akhtar Malik, Ali Kamran, Muhammad Umar Qaiser, Samra Riaz (Journal of Rawalpindi Medical College, 2022)
Objective: To determine the diagnostic accuracy of Tzanakis and Alvarado score for the diagnosis of acute appendicitis taking histopathology as the gold standard. Materials and Methods: It was a Cross-sectional validation study The study was carried out at the emergency department of RMC allied hospital Rawalpindi. The study was completed in eighteen months from 1st May 2016 till 30th Nov 2017. After approval from the ethical committee total of 420 patients fulfilling inclusion criteria from the emergency department of District head Quarter hospital, Rawalpindi was taken. Informed consent was taken from patients or their attendants, and their demographic information like name, age, sex, and address was obtained. Alvarado score and Tzanakis score were calculated (as per operational definition) at the time of admission of the patients. After surgery, the specimen appendix was sent for histopathology in the hospital lab. The diagnosis of the acute appendix was based on a positive histological report which was verified by a pathologist. All the data was entered by a researcher who will collect the data by himself. Results: The mean age of patients in this study was 20.15±7.13 years with 218 (51.9%) males and 202 (48.1%) females. The mean Alvardo score was recorded as 7.22±1.58 with the mean Tzanakis score being 9.64±3.13. The histopathology for diagnosing appendicitis showed positive for 367 (87.4%) patients and negative for 53 (12.6%) patients. The sensitivity of Alvarado score for diagnosing appendicitis, keeping histopathology as the gold standard was 86.92%, specificity was 92.45%, Positive Predictive Value was 98.76%, and Negative Predictive Value was 50.52% and overall diagnostic accuracy was 87.62%. The sensitivity of the Tzanakis score for diagnosing appendicitis, keeping histopathology as the gold standard was 88.83%, specificity was 88.6%, Positive Predictive Value was 98.19%, Negative Predictive Value was 53.41% and overall diagnostic accuracy was 88.81%. Conclusion: The sensitivity of the Tzanakis score was high when compared to the Alvarado score. And specificity was high in the Alvarado score when compared to the Tzanakis score. Moreover, the overall diagnostic accuracy of the Tzanakis score was high when compared to the Alvarado score. SoTzanakis score can be utilized to predict appendix and in the future, we can avoid negative appendectomies.